Severe COVID-19, Another Piece in the Puzzle of the Hyperferritinemic Syndrome. An Immunomodulatory Perspective to Alleviate the Storm - Ruscitti, Piero; Berardicurti, Onorina; Di Benedetto, Paola; Cipriani, Paola; Iagnocco, Annamaria; Shoenfeld, Yehuda; Giacomelli, Roberto (Frontiers in Immunology, 2020)
The coronavirus disease 2019 (COVID-19), an acute respiratory disease caused by SARS-CoV-2, has declared as a public worldwide health emergency. Interestingly, severe COVID-19 is characterised by fever, hyperferritinemia, and hyper-inflammatory process with massive release of pro-inflammatory cytokines, which may be responsible for high rate of mortality. These findings may advocate a similarity between severe COVID-19 and some challenging rheumatic diseases, such as adult onset Still’s disease, secondary haemophagocytic lymphohistiocytosis, and catastrophic anti-phospholipid syndrome, which have been included in the “hyperferritinaemic syndrome”. Furthermore, as performed in these hyper-inflammatory states, COVID-19 may probably benefit by immunomodulatory therapies.